Efficacy of belimumab in two serologically distinct high disease activity subgroups of patients with systemic lupus erythematosus: post-hoc analysis of data from the phase III programme. Issue 1 (10th February 2021) - Maslen, Toni; Bruce, Ian N; D'Cruz, David; Ianosev, Mihaela; Bass, Damon L; Wilkinson, Christel; Roth, David A
Abstract : Objective: To assess the appropriateness of expanded serological activity eligibility criteria for belimumab use in the UK systemic lupus erythematosus (SLE) population (and possibly other countries), which includes patients with either anti-double-stranded DNA (anti-dsDNA) positivity or hypocomplementaemia rather than both criteria. Methods: This post-hoc analysis used data from three randomised, double-blind, placebo-controlled phase III belimumab trials: BLISS-52 (BEL110752; NCT00424476 ), BLISS-76 (BEL110751; NCT00410384 ) and BLISS-SC (BEL112341; NCT01484496 ). Patients with SLE were stratified by high disease activity (HDA): HDA1, Safety of Estrogens in Lupus Erythematosus National Assessment-SLE Disease Activity Index (SELENA-SLEDAI) score ≥10, low complement and positive anti-dsDNA; and HDA2, SELENA-SLEDAI ≥10 and either low complement or positive anti-dsDNA. Results: This analysis included 660 HDA1 patients (n=396 on intravenous treatment; n=264 on subcutaneous treatment) and 969 HDA2 patients (n=532 on intravenous treatment; n=437 on subcutaneous treatment). Significant improvements were observed at week 52 with belimumab versus placebo, irrespective of subgroups or drug formulations, in SLE Responder Index (SRI) 4 response (OR (95% CI): HDA1 intravenous 2.7 (1.8 to 4.1); HDA2 intravenous 2.3 (1.61 to 3.26); HDA1 subcutaneous 2.2 (1.22 to 3.85); HDA2 subcutaneous 1.8 (1.17 to 2.74)); proportion of patients achieving ≥4-point reduction in SELENA-SLEDAI score (OR (95% CI): HDA1 intravenous 2.6 (1.7 to 3.9); HDA2 intravenous 2.1 (1.49 to 3.03); HDA1 subcutaneous 2.3 (1.30 to 4.14); HDA2 subcutaneous 1.9 (1.21 to 2.84)); patients with no worsening in Physician Global Assessment (OR (95% CI): HDA1 intravenous 2.0 (1.3 to 3.1); HDA2 intravenous 1.7 (1.17 to 2.45); HDA1 subcutaneous 2.3 (1.18 to 4.40); HDA2 subcutaneous 1.8 (1.11 to 2.92)); and risk of severe flares (HR (95% CI): HDA1 intravenous 0.6 (0.37 to 0.81); HDA2 intravenous 0.6 (0.43 to 0.86); HDA1 subcutaneous 0.52 (0.30 to 0.92); HDA2 subcutaneous 0.59 (0.37 to 0.94)). Conclusion: Broadening the HDA population to include either low complement or positive anti-dsDNA, rather than both, would enable more UK patients to receive SLE treatment and experience improved clinical outcomes.